DEVELOPMENT OF HIGH-PERFORMING NOVEL HETEROGENEOUS FENTON-LIKE CATALYSTS FOR THE ABATEMENT OF ORGANIC POLLUTANTS: AN OVERVIEW - Ameta, Chetna; Jain, Abhilasha (Journal of the Chilean Chemical Society, 2023)
Fenton reagent is known for over a hundred years and the role of homogeneous and heterogeneous Fenton degradation in wastewater treatment in removing recalcitrant organic contaminants is well appreciated and extensively explored. Limitations and shortcomings of homogeneous and heterogeneous Fenton degradation hinder the large-scale application of heterogeneous Fenton reactions in environmental remediation. Thus, the development of Fenton-like reagents is considered as a need of the hour. Most of the drawbacks of Fenton degradation have been taken care of by these novel reagents were dramatically increased catalytic degradation rate of contaminants was observed due to high surface area. Good mechanical stability, improved electron transfer, magnetically separability, and the possibility of widening the scope are the additional features of Fenton-like reagents. In this review, recent trends in the synthesis, strategies for enhancing its catalytic activity, and various applications of heterogeneous Fenton-like catalysts for the abatement of organic pollutants are discussed. This review describes the recent development of other transition metals, Graphene oxide/Carbon/CNT, MIL/MOF, and oxides as Fenton like catalysts in environmental remediation procedures even at ambient conditions. This review aims to encourage the fabrications of novel and efficient heterogeneous Fenton-like systems and assist the readers in the selection of the best suitable Fenton-like systems for industrial applications by unfolding the various properties and applications of these catalysts.